2019
DOI: 10.1021/acs.orglett.9b02462
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Allylation of Amides with Styrenes Using DMSO as Both the Solvent and the α-Methylene Source

Abstract: An efficient synthesis of privileged allylic amines has been developed via cobalt-catalyzed allylation of amides with styrenes, in which DMSO was used as both the solvent and the α-methylene source. This transformation features high yields, and selectivity for the (E)-isomer of the linear product. Through the experimental and computational investigations, a sequential K 2 S 2 O 8 -mediated oxidative coupling/cobalt-assisted regioselective alkene insertion/β−H elimination/alkene dissociation/hydride transfer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Apart from Cu(OTf) 2 , other catalysts such as TfOH, TsOH, K 2 CO 3 , Et 3 N, FeCl 3 , ZnCl 2 , Cu(OAc) 2 and Pd(OAc) 2 at 10 mol% were also employed in the protocol and it was clear that the most efficient catalyst in the present catalytic system was Cu(OTf) 2 (entry 7 vs [11][12][13][14][15][16][17][18]. Further investigation of the amount of the catalyst indicated that 10 mol% was an ideal amount (entry 7 vs [19][20]. The effect of reaction temperatures on the yields was then investigated.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Apart from Cu(OTf) 2 , other catalysts such as TfOH, TsOH, K 2 CO 3 , Et 3 N, FeCl 3 , ZnCl 2 , Cu(OAc) 2 and Pd(OAc) 2 at 10 mol% were also employed in the protocol and it was clear that the most efficient catalyst in the present catalytic system was Cu(OTf) 2 (entry 7 vs [11][12][13][14][15][16][17][18]. Further investigation of the amount of the catalyst indicated that 10 mol% was an ideal amount (entry 7 vs [19][20]. The effect of reaction temperatures on the yields was then investigated.…”
Section: Resultsmentioning
confidence: 89%
“…[18] Very recently, Yi et al reported cobalt-catalyzed allylation of amides using DMSO as both the solvent and the methylene source. [19] Talukdar demonstrated Ru(II) photo-catalyzed synthesis of acetals from alcohols by DMSO. [20] In addition, a cascade [4 + 1] annulation of sulfonium salts for synthesis of polyfunctional furans using DMSO as one carbon source was established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, DMSO dehydrates to form intermediate 1 with an S=C bond [30a,b,f] . 1 a then undergoes a nucleophilic addition reaction with 1 to produce intermediate 2 , [30e] and simultaneously loses methyl mercaptan to obtain imine 3 [30f] as identified by high performance liquid chromatography‐mass spectrometry (LC‐MS) (see support information). Next, 3 [30f] is protonated to form a carbenium ion intermediate 4 [23] .…”
Section: Resultsmentioning
confidence: 99%
“…The construction of suitably functionalized amide frameworks is useful in many industrial and natural product syntheses . In the past few decades, many traditional approaches for transition-metal-catalyzed hydroamination of N -heterocycles and primary/secondary amines with alkynes and alkenes have been well explored. Base-mediated nucleophilic addition of heterocycles as well as amine moieties has also been known from many renowned reactions reported in the literature. , However, due to the formation of highly stable resonating structures and poor nucleophilicity hydroamination of amides is still challenging. …”
mentioning
confidence: 99%